Metallophthalocyanines bearing four 3-(pyrrol-1-yl)phenoxy units as photosensitizer for dye-sensitized solar cells - Polat, Merve Pamukcu; Yenilmez, H. Yasemin; Koca, Atif; Altindal, Ahmet; Bayir, Zehra Altuntas (ELSEVIER SCI LTD, 2018)
In this article, the synthesis of non-peripheral metallophthalocyanines (cobalt, zinc, and manganese) bearing four 3-(pyrrol-1-yl)phenoxy units was reported. The new compounds have been characterized using UV-Vis, FTIR, H-1 NMR, and mass spectroscopic data. Aggregation behaviors of phthalocyanines were investigated in concentrations ranging from 14 x 10(-6) to 2 x 10(-6) M. Electrochemical measurements gave well illustrated redox activities of MnClPc and CoPc. Electrochemical and spectroelectrochemical studies showed that MnClPc gives two metal-based reduction processes in addition to the one ring-based reduction and one ring-based oxidation process. Distinct color differences between the electrogenerated MnClPc species were observed during in situ spectroelectrochemical measurements. The potential of these compounds as photosensitizers and dependence of the photovoltaic performance on the thickness of photoanode layer were investigated. For this purpose, DSSC devices were fabricated with the structure of FTO/TiO2:4-6/Electrolyte/Pt/FTO and characterized under AM 1.5 illuminations. By using 6 as dye a photovoltaic conversion efficiency of 2.44% with short circuit current density of 7.17 mA cm(-2) and open circuit voltage of 0.68 V was observed.
Keywords: Phthalocyanine; Non-peripheral; Pyrrole; Photosensitizer; Electrochemistry; Spectroelectrochemistry; DSSC; ZINC PHTHALOCYANINE COMPLEXES; ELECTROCHEMICAL PROPERTIES; SUBSTITUTED COBALT; SPECTROELECTROCHEMICAL CHARACTERIZATION; COPPER PHTHALOCYANINES; TIO2 FILMS; MANGANESE; AGGREGATION; IRON; EFFICIENCY; Chemistry; Engineering; Materials Science